2019
DOI: 10.1002/bab.1807
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 removal by three bacterial strains and optimization of fermentation process parameters

Abstract: Aflatoxin B1 (AFB1) removing bacterial strains were isolated from different habitats that were easily contaminated by AFB1. Furthermore, the composition of the fermentation medium and conditions of fermentation process were optimized, including carbon source, nitrogen source, metal ions, temperature, initial pH value, inoculation volume, and culture broth volume. Using coumarin as the sole carbon and energy source, we primarily screened 31 strains, and 10 strains were found to be capable to remove AFB1. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…As a report has demonstrated that Klebsiella sp. degrades AF [ 18 ], the AF degradation activity of the strain KTTM was examined. When AFB 1 was added to a liquid medium and the strain KTTM was cultured in the medium for 3 days, the concentration of AFB 1 in the culture broth was consistent with that of the control in which AFB 1 was kept in the liquid medium without inoculation of the bacterium for 3 days ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a report has demonstrated that Klebsiella sp. degrades AF [ 18 ], the AF degradation activity of the strain KTTM was examined. When AFB 1 was added to a liquid medium and the strain KTTM was cultured in the medium for 3 days, the concentration of AFB 1 in the culture broth was consistent with that of the control in which AFB 1 was kept in the liquid medium without inoculation of the bacterium for 3 days ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The culture supernatant of two Klebsiella sp. strains was reported to degrade AF [ 18 ], as the amount of AF decreased by approximately 70% after incubation with the culture supernatant for 3 days. Compared to the activity of the reported strains, that of the strain KTTM was weak.…”
Section: Discussionmentioning
confidence: 99%